Study on the absorption characteristics of euscaphic acid and tiliroside in fruits of Rosa laxa Retz. - Ning Wang; Li Tian (PeerJ)
The fruits of Rosa laxa Retz. (FRL) have a long history of medicinal use, known for their rich composition of flavonoids, polyphenols, amino acids, sugars, and other bioactive compounds. FRL exhibits pharmacological effects such as antioxidant, antiviral, antibacterial, and antitumor activities, making it a valuable resource with significant development potential in both the food and pharmaceutical industries. This study employed a response surface methodology combined with ultra-high-performance liquid chromatography-triple quadrupole mass spectrometry (UPLC-TQ-MS) to optimize FRL extraction. Reflux extraction was determined to be the most effective method with the following optimized parameters: 65% ethanol extraction solvent, material-to-liquid ratio of 1:35 (g/mL), and extraction time of 140 min, resulting in the FRL extract (FRLE). Under these optimized conditions, the extracted amount was extract was 51.00 ± 1.07%, the average content of total polyphenols was 126.55 ± 2.61 mg/g, and the average content of euscaphic acid was 2.90 ± 0.08 mg/g, demonstrating the efficiency of the extraction method. Using the Caco-2 cell model, the study investigated the absorption characteristics of euscaphic acid and tiliroside within FRLE. Results indicated that with increasing time, the absorbed amount (Qr) of euscaphic acid and tiliroside gradually increased, with an efflux ratio (RB→A/A→B) of less than 1.5, suggesting bidirectional drug transport with no significant directionality. Upon the addition of P-glycoprotein (P-gp) inhibitors Verapamil (Ver) and Ciclosporin A (CsA), as well as the chelating agent ethylenebis (oxyethylenenitrilo) tetraacetic acid (EGTA), Qr and Papp values notably increased, indicating that these two components are P-gp substrates with cellular basolateral efflux transport. Additionally, optimal absorption efficiency was observed under weakly acidic conditions (pH 6.0). In conclusion, euscaphic acid and tiliroside in FRLE demonstrated good membrane permeability, primarily relying on passive diffusion for absorption. This study offers experimental insights into the intestinal absorption of FRL in vivo.